ANALISIS LEVEL OF SERVICE (L.O.S): STUDI KASUS DI JALAN DRS. ESAU SESA, KABUPATEN MANOKWARI, PROVINSI PAPUA BARAT - Riris Setyowati; Pribowo Angling Kusumo (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
Jalan Drs. Esau Sesa is a non-shared two-way connecting road owned by the Manokwari Regency Government, Papua Barat Province. This road is the main road that connects between districts with a road width of + 6 meters. The rapid development of land use along with Drs. Esau Sesa has the potential to reduce road service levels. Field observations showed that commercial activities are high in this area. Thus the traffic activities, as well as parked vehicles are also high, exceeding the facilities capacities. This condition is one of the causes of traffic jams on the road. Based on the data analysis results, Jalan Drs. Esau Sesa has a Road Capacity (C) of 2,061 vehicles/hour with a Free Flow Velocity (FV) of 45,315 Km/hour and a Degree of Saturation (DS) of 0.808. These results are equivalent to the Level of Service (L.O.S) at level D which means traffic flow on Jalan Dr. Esau Sesa began to become unstable, with low traffic jams with creeping currents and vehicle volumes approaching maximum capacity.